2016
DOI: 10.3748/wjg.v22.i34.7692
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of colorectal peritoneal carcinomatosis: Role of the peritoneum

Abstract: Colorectal cancer (CRC) is the third most common cancer and the fourth most common cause of cancer-related death worldwide. Besides the lymphatic and haematogenous routes of dissemination, CRC frequently gives rise to transcoelomic spread of tumor cells in the peritoneal cavity, which ultimately leads to peritoneal carcinomatosis (PC). PC is associated with a poor prognosis and bad quality of life for these patients in their terminal stages of disease. A loco-regional treatment modality for PC combining cytore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 171 publications
4
89
0
1
Order By: Relevance
“…At the same time, however, stent mechanical stress might cause long-term effects on tumour cell spreading; therefore, the debate on BTS persists [15,19,24,34,35,56]. Related studies have shown that mechanical friction of the colonoscope and guidewire, mechanical expansion after stent release, and stent-related perforation during stenting can lead to the localised spreading of tumour cells and dissemination through blood and lymphatic vessels [57,58]. Sterne et al found that the expression of cytokeratin 20 was significantly increased in peripheral venous blood after stent implantation [59], and Maruthachalam et al demonstrated that the circulating levels of CEA and CK20 mRNA were significantly increased after colon stenting [15]; Higgins-Julian and Kim et al found that the invasion rate of nerves and lymph nodes increased after implantation of SEMS, but no difference in survival rate was found compared with emergency surgery.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, however, stent mechanical stress might cause long-term effects on tumour cell spreading; therefore, the debate on BTS persists [15,19,24,34,35,56]. Related studies have shown that mechanical friction of the colonoscope and guidewire, mechanical expansion after stent release, and stent-related perforation during stenting can lead to the localised spreading of tumour cells and dissemination through blood and lymphatic vessels [57,58]. Sterne et al found that the expression of cytokeratin 20 was significantly increased in peripheral venous blood after stent implantation [59], and Maruthachalam et al demonstrated that the circulating levels of CEA and CK20 mRNA were significantly increased after colon stenting [15]; Higgins-Julian and Kim et al found that the invasion rate of nerves and lymph nodes increased after implantation of SEMS, but no difference in survival rate was found compared with emergency surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The vasculature is organized in a single layer and the microvessels are arranged relatively spaciously, resulting in a low vessel density. This low vessel density possibly affects pathological processes such as the restrictive growth of metastases on the peritoneal membrane [8, 10]. Interestingly, not only the density, but also the peritoneal flow parameters (PPV, MFI) were significantly lower when compared to the sublingual microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, surgical trauma or inflammation and subsequent adhesion formation and fibrosis can decrease diffusion capacity, cause pain, impair female fertility, and hamper surgical interventions [4-6]. If the peritoneum is affected by metastases of gastrointestinal or gynecological malignancies, this ultimately leads to peritoneal carcinomatosis, which is associated with a poor clinical outcome [7, 8]. In case of endometriosis, endometrial tissue can affect the pelvic peritoneum, occasionally requiring surgery because of pain and infertility [9].…”
Section: Introductionmentioning
confidence: 99%
“…In pathological processes, such peritoneal carcinomatosis, the information about the sheets of the involved sub-spaces will assist in the estimation of the peritoneal surface affected by the pathology, and it will be possible to evaluate the treatment, such as resections of the affected peritoneum (Deraco et al, 2009;Baratti et al, 2015;Mangeolle et al, 2018;Sugarbaker, 2018) and chemotherapy (Bijelic et al, 2007;Lemoine et al, 2016;Kerbage et al, 2018;Lagast et al, 2018).…”
Section: From the Values Inmentioning
confidence: 99%